2018
DOI: 10.1099/jmm.0.000724
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with pneumococcal neuraminidases NanA, NanB and NanC to generate neutralizing antibodies and to increase survival in mice

Abstract: We recommend the inclusion of three pneumococcal neuraminidases in future protein vaccine formulations to prevent invasive pneumococcal infection caused by various serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…A combination of intact or truncated LytA, CbpJ, NanA, and BgaA may be attractive antigen candidates for the development of a universal pneumococcal vaccine. Several groups have already reported that individually, NanA and LytA work as protective antigens in mouse infection models (Berry et al, 1989;Lock et al, 1992;Long et al, 2004;Tong et al, 2005;Yuan et al, 2011;Janapatla et al, 2018). On the other hand, as non-pathogenic native microflora and other S. mitis group species also contain some of these genes, it is necessary to examine the possibility that the vaccine may alter the composition of oral and/or lung microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of intact or truncated LytA, CbpJ, NanA, and BgaA may be attractive antigen candidates for the development of a universal pneumococcal vaccine. Several groups have already reported that individually, NanA and LytA work as protective antigens in mouse infection models (Berry et al, 1989;Lock et al, 1992;Long et al, 2004;Tong et al, 2005;Yuan et al, 2011;Janapatla et al, 2018). On the other hand, as non-pathogenic native microflora and other S. mitis group species also contain some of these genes, it is necessary to examine the possibility that the vaccine may alter the composition of oral and/or lung microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence genes are crucial candidate targets for the development of next-generation protein vaccines. For instance, a study reported that generate neutralizing antibodies immunization with pneumococcal neuraminidases nanA, nanB , and nanC was able to increase survival in mice (Janapatla et al, 2018). Our results showed that there is a high prevalence in nanA, piaA, lytA, ply, psaA, pavA, spxB, htrA and clpP whereas lower in cps2A, cbpA , and pspA .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pneumococcal proteins have been comparatively well investigated as promising targets for future non-serotype-specific protein-based pneumococcal vaccines, such as pneumococcal surface protein A (PspA) [17,18], pneumococcal surface protein C (PspC) [19,20], pneumococcal choline-binding protein (PcpA) [21], three neuraminidases (NanA, NanB, and NanC) [22,23], pneumolysin (Ply) [24], and four pneumococcal histidine triad proteins (PhtA, PhtB, PhtD, and PhtE) [25][26][27][28]. At present, an investigational pneumococcal vaccine is undergoing Phase I/II clinical trials in infants [29,30], children [31], and adults [32].…”
Section: Introductionmentioning
confidence: 99%